Comparison of Metarhizium isolates for biocontrol of helicoverpa armigera (Lepidoptera : Noctuidae) in chickpea - Kulkarni, Shuklangi A.; Ghormade, Vandana; Kulkarni, Girish; Kapoor, Manisha; Chavan, Santosh B.; Rajendran, Armugam; Patil, Sanjay K.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
Metarhizium isolates from soil (53) and insect hosts (10) were evaluated for extracellular production of cuticle degrading enzyme (CDE) activities such as chitinase, chitin deacetylase (CDA), chitosanase, protease and lipase. Regression analysis demonstrated the relation of CDE activities with Helicoverpa armigera mortality. On basis of this relation, ten isolates were selected for further evaluation. Subsequently, based on LT(50) of the 10 isolates towards H. armigera, five isolates were selected. Out of these five isolates, three were selected on the basis of higher conidia production (60-75 g/kg rice), faster sedimentation time (ST(50)) (2.3-2.65 h in 0.1% (w/v) Tween 80) and lower LC(50) (1.4- 5.7 x 10(3) conidia/mL) against H. armigera. Finally, three Metarhizium isolates were selected for the molecular fingerprinting using ITS sequencing and RAPD patterning. All three isolates, M34412, M34311 and M81123, showed comparable RAPD patterns with a 935G primer. These were further evaluated for their field performance against H. armigera in a chickpea crop. The percent efficacies with the three Metarhizium isolates were from 65 to 72%, which was comparable to the chemical insecticide, endosulfan (74%).
Keywords: appressorium formation; chitin deacetylase; chitinase; chitosanase; Helicoverpa armigera; Lipase; Metarhizium anisopliae; Protease

Effect of repeated in vitro sub-culturing on the virulence of metarhizium anisopliae against helicoverpa armigera (Lepidoptera : Noctuidae) - Nahar, Pallavi B.; Kulkarni, Shuklangi A.; Kulye, Mahesh S.; Chavan, Santosh B.; Kulkarni, Girish; Rajendran, Armugham; Yadav, Priya D.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
The effect of repeated conidial sub-culturing of Metarhizium anisopliae on its virulence against Helicoverpa armigera (Hbner) was studied. The LT(50) observed against third instar larvae of H. armigera for the first sub-culture was 3.4 days; it increased to 4.5 and 5.6 days for the 20th and the 40th sub-cultures, respectively. The LT50 values after passage of the 40th sub-culture on H. armigera decreased to 4.4 and 3.7 days for the 40th (first in vivo) and the 40th (fifth in vivo) passages, respectively. Similarly, the LC(50) of M. anisopliae towards third instar larvae of H. armigera increased from the first sub-culture (0.17x10(4)) to (3.0x10(4)) for the 40th conidial transfers on potato dextrose agar and again decreased to 0.74x10(4) and 0.23x10(4) in the 40th (first in vivo) and the 40th (fifth in vivo) passage, respectively. Similar trends for LC(50) and LT(50) values were seen when sugarcane woolly aphid, Ceratovacuna lanigera Zehntner was used as a host. Significant variation in appressorium formation and cuticle-degrading enzyme production such as chitinase, chitin deacetylase, chitosanase and protease during subsequent sub-culturing and passage through H. armigera was observed. Though there was no effect on internal transcribed spacer (ITS) sequence pattern, interestingly, in randomly amplified polymorphic DNA (RAPD), significant differences in the band intensities and in the banding pattern for different sub-cultures of M. anisopliae were observed. As stable virulence towards the insect pest is desirable for commercialisation of a mycoinsecticide, such changes in virulence due to repeated in vitro transfer need to be monitored and minimised.
Keywords: appressorium formation; chitin deacetylase; chitinase; Helicoverpa armigera; in vitro sub-culturing; Lipase; Metarhizium anisopliae; Protease

Development of mycoinsecticide for the control of insect pests: comparative evaluation of metarhizium isolates to identify strains for commercialization - Deshpande, Mukund V.; Kulkarni, Shuklangi A.; Ghormade, Vandana; Kapoor, Manisha; Chavan, Santosh B.; Kulkarni, Grish; Shouche, Yogesh (New Biotechnology, 2009)